Amino-Terminal Processing of Helicobacter pylori Serine Protease HtrA: Role in Oligomerization and Activity Regulation - Albrecht, Nicole; Tegtmeyer, Nicole; Sticht, Heinrich; Skórko-Glonek, Joanna; Backert, Steffen (Frontiers in Microbiology, 2018)
The HtrA family of serine proteases is found in most bacteria, and plays an essential role in the virulence of the gastric pathogen Helicobacter pylori. Secreted H. pylori HtrA (HtrAHp) cleaves various junctional proteins such as E-cadherin disrupting the epithelial barrier, which is crucial for bacterial transmigration across the polarized epithelium. Recent studies indicated the presence of two characteristic HtrAHp forms of 55 kDa and 52 kDa (termed p55 and p52, respectively), in worldwide strains. In addition, p55 and p52 were produced by recombinant HtrAHp, indicating auto cleavage. However, the cleavage sites and their functional importance are yet unclear. Here, we determined the amino-terminal ends of p55 and p52 by Edman sequencing. Two proteolytic cleavage sites were identified (H46/D47 and K50/D51). Remarkably, the cleavage site sequences are conserved in HtrAHp from worldwide isolates, but not in other Gram-negative pathogens, suggesting a highly specific assignment in H. pylori. We analyzed the role of the amino-terminal cleavage sites on activity, secretion and function of HtrAHp. Three-dimensional modelling suggested a trimeric structure and a role of amino-terminal processing in oligomerization and regulation of proteolytic activity of HtrAHp. Furthermore, point and deletion mutants of these processing sites were generated in the recently reported Campylobacter jejuni ΔhtrA/htrAHp genetic complementation system and the minimal sequence requirements for processing were determined. Polarized Caco-2 epithelial cells were infected with these strains and analyzed by immunofluorescence microscopy. The results indicated that HtrAHp processing strongly affected the ability of the protease to disrupt the E-cadherin-based cell-to-cell junctions. Casein zymography confirmed that the amino-terminal region is required for maintaining the proteolytic activity of HtrAHp. Furthermore, we demonstrated that this cleavage influences the secretion of HtrAHp in the extracellular space as an important prerequisite for its virulence activity. Taken together, our data demonstrate that amino-terminal cleavage of HtrAHp is conserved in this pathogen and affects oligomerization and thus, secretion and regulatory activities, suggesting an important role in the pathogenesis of H. pylori.